2018
DOI: 10.1371/journal.pone.0199258
|View full text |Cite
|
Sign up to set email alerts
|

Anti-replicative recombinant 5S rRNA molecules can modulate the mtDNA heteroplasmy in a glucose-dependent manner

Abstract: Mutations in mitochondrial DNA are an important source of severe and incurable human diseases. The vast majority of these mutations are heteroplasmic, meaning that mutant and wild-type genomes are present simultaneously in the same cell. Only a very high proportion of mutant mitochondrial DNA (heteroplasmy level) leads to pathological consequences. We previously demonstrated that mitochondrial targeting of small RNAs designed to anneal with mutant mtDNA can decrease the heteroplasmy level by specific inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…To counter the problem of low efficiency, new RNA molecules can be created with greater mitochondrial import capacities, and our previous reports indicate that it is possible. As a matter of fact, our recent studies with 5S rRNA based RNA vectors clearly are supporting this strategy, as increasing expression and import of recombinant RNA also produce a more pronounced anti‐replication effect on mtDNA . All in all, we believe that the current study provides matter to be moderately optimistic about the possibility of CRISPRization of human mitochondrial DNA.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…To counter the problem of low efficiency, new RNA molecules can be created with greater mitochondrial import capacities, and our previous reports indicate that it is possible. As a matter of fact, our recent studies with 5S rRNA based RNA vectors clearly are supporting this strategy, as increasing expression and import of recombinant RNA also produce a more pronounced anti‐replication effect on mtDNA . All in all, we believe that the current study provides matter to be moderately optimistic about the possibility of CRISPRization of human mitochondrial DNA.…”
Section: Discussionsupporting
confidence: 58%
“…C ,D, both transient and induced expression of MTS COX8A ‐hCas9 do not significantly influence mtDNA copy number. Finally, it is worth to mention that our previous assays in the frame of the anti‐replicative strategy to address heteroplasmic mtDNA mutations proved to be more effective when imported recombinant RNAs with higher melting temperatures were applied , which can indirectly indicate that the temperature issue is to be seriously taken into account also for CRIPRization.…”
Section: Discussionmentioning
confidence: 93%
“…Our results show an enhanced delivery of gRNA with RP-loop. A recent study has shown that guide RNA with short hairpin structures can promote mitochondrial import and specific cleavage of mtDNA albeit at low level due to limited import into mitochondrial matrix (41,42). This study further strengthens our hypothesis that specific hairpin structures that are involved in the delivery of nuclear encoded RNA can serve as potential adapter for delivery and PNPase may serve as conduit for channeling this recombinant RNA into mitochondrial matrix.…”
Section: Discussionsupporting
confidence: 86%
“…Our results show an enhanced delivery of sgRNA with RP loop into the mitochondria. A recent study has shown that guide RNA with short hairpin structures can promote mitochondrial import and specific cleavage of mtDNA albeit at a low level due to limited import into the mitochondrial matrix ( Loutre et al, 2018a , b ). This study further strengthens our hypothesis that specific hairpin structures that are involved in the delivery of nuclear-encoded RNA can serve as potential adapter for delivery, and PNPase may serve as a conduit for channeling this recombinant RNA into the mitochondrial matrix.…”
Section: Discussionmentioning
confidence: 99%